Legal Protection of Notary Officials according to Indonesian positive law - Rahim, Yulfita; Syafrinaldi, Syafrinaldi; Thamrin, S.; Susanti, Heni (Technium Social Sciences Journal, 2022)
Notary public in carrying out their profession to provide services and legal services to the community need to get protection and guarantees in order to achieve legal certainty. Guarantee of protection and guarantee of legal certainty on the implementation of notary duties and functions has been stipulated in the Law of the Republic of Indonesia Number 2 of 2014 concerning Amendments to Law No. 30 of 2004 concerning Notarial Positions. This change in the legal basis is intended to further affirm and strengthen the duties, functions, and authority of notary public officials as well as synchronize with other laws. The role of the Notary Department in Indonesia as well as in Pekanbaru City is very important for the community in solving various legal problems faced by the community, one of which is in issuing authentic deed. The professional rights of notary positions, especially regarding civil rights, ideally should get legal protection in carrying out their profession, but in fact Notaries in carrying out their duties often do not get legal protection as they should, as a result notary are faced with civil or criminal legal proceedings.